2010
DOI: 10.1111/j.1600-0528.2010.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

How primary care dentists perceive and are influenced by research

Abstract: Dentists wanted concise, timely evidence-based guidance to aid their management of patients. Further research needs to be undertaken to understand how to develop an evidence-based culture in primary dental care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…These general dental practices were already busy and few of them had participated in research before. 6,7 Why attempt such a challenge? For the primary care dentist faced with the prospect of managing a child with caries, there is little direct evidence to guide their decisions.…”
Section: Introductionmentioning
confidence: 99%
“…These general dental practices were already busy and few of them had participated in research before. 6,7 Why attempt such a challenge? For the primary care dentist faced with the prospect of managing a child with caries, there is little direct evidence to guide their decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers in this area have focused on the facilitators and barriers to implementing EBD in practice (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The published research suggests that dentists are apprehensive and fear losing autonomy, which delays the adoption of EBD in practice (6,8,9,13).…”
mentioning
confidence: 99%
“…The published research suggests that dentists are apprehensive and fear losing autonomy, which delays the adoption of EBD in practice (6,8,9,13). Dentists claim that they lack time to seek out research evidence, and argue that this evidence does not provide clear answers to important clinical questions (2,6,8,9,(12)(13)(14). Some studies have suggested that dentists' clinical performance does not change as a result of being provided with evidence-based knowledge (7,(15)(16)(17); others that evidence-based dental care is more likely to be adopted if already used by dentists' peers (10).…”
mentioning
confidence: 99%
“…The latter theme and its codes have been reported separately 21 so this paper is limited to the first six codes associated with undertaking prospective studies and clinical trials in practice. For the busy practitioner, involvement in clinical research was seen as yet another burden, especially if patients' treatments were delayed because of the need to follow the protocol.…”
Section: Resultsmentioning
confidence: 99%